Cochlear Implantation for Children and Adults with Severe-to-Profound Hearing Loss - Entwisle, Lavin K.; Warren, Sarah E.; Messersmith, Jessica J. (Seminars in Hearing, 2018)
Cochlear implants (CIs) have proven to be a useful treatment option for individuals with severe-to-profound hearing loss by providing improved access to one's surrounding auditory environment. CIs differ from traditional acoustic amplification by providing information to the auditory system via electrical stimulation. Both postlingually deafened adults and prelingually deafened children can benefit from a CI; however, outcomes with a CI can vary. Numerous factors can impact performance outcomes with a CI. It is important for the audiologist to understand what factors might play a role and impact performance outcomes with a CI so that they can effectively counsel the recipient and their family, as well as establish appropriate and realistic expectations with a CI. This review article will discuss the CI candidacy process, CI programming and postoperative follow-up care, as well as considerations across the lifespan that may affect performance outcomes with a CI.
Keywords: cochlear implant; cochlear implant candidacy; cochlear implant outcomes